A novel visible light sensing and recording system enabled by integration of photodetector and electrochromic devices. Issue 20 (14th May 2021) - Wu, Wenqiang; Zhou, Mengmeng; Li, Dong; Li, Shengman; Yang, Zheng; Huo, Zhihao; Wu, Yanqing; Tan, Yongwen; Han, Xun; Pan, Caofeng; Pan, Anlian
Abstract : A novel visible light sensing and recording system was fabricated by the integration of photodetectors with electrochromic devices, which achieves the recording of visible light patterns in the form of color display. Abstract : The integration of multiple electronic or optoelectronic devices is an effective strategy to use their unique functions to realize a specific goal. A state-of-the-art photodetector (PD) array can realize real-time image sensing, but the image information will disappear immediately with the removal of the light stimuli. Here, we design a visible light sensing and recording system by the integration of a perovskite PD array with a tungsten trioxide-based electrochromic device (ECD) array (10 × 10 pixels). The system can convert the received visible light signals into electrical signals to change the storable color of the corresponding pixels in the ECD array, thus realizing optical information recording in the form of the color display. As a conceptual demonstration, the system achieves the recording of the "H"-shaped visible light pattern projected to the active area of the PD array. Besides, after removing the illumination stimuli, the recording of the light pattern continues in the absence of the power supply owing to the "color memory effect". The recorded length can be regulated through the periods of illumination stimulation. The proof-of-concept system may have potential applications in image sensors, electronic eyes, and intelligent electronics.